Regioselective Biotransformation of Phloretin Using Streptomyces avermitilis MA4680 - Kim, Wooil; Lee, Jong ki; Choi, Kwon Young; Kim, Byung Gee; Kim, Junehyung (Biotechnology and Bioprocess Engineering, 2020)
Streptomyces avermitilis MA4680 was used for the biotransformation of phloretin, one of the dihydrochalcone found in apple bark. After LC analysis, two main biotransformed products were identified and they were further analyzed using GC/MS. After BSTFA derivatization of biotransformed product, they were interpreted as regioselectively hydroxylated products of phloretin in Bring. Maximum conversion of phloretin was 6.7% with 1 h of reaction, and the phloretin and reaction products were completely metabolized after 3 h of reaction due to cellular metabolism. Addition of 0.5 mM quinidine completely blocked hydroxylation of phloretin, which means the hydroxylation proceed by P450 monoxygenase dependent metabolism. Addition of Brij 35 detergent resulted in 150% increase of hydroxylated product due to facilitating transport of phloretin and its reaction product across cellular membrane.
Keywords: Brij 35; Cellular membranes; Cellular metabolism; Derivatizations; Dihydrochalcone; Phloretin; Regio-selective; Streptomyces avermitilis; biotransformation; flavonoid; hydroxylation; phloretin